Evaluation of the Implementation of the Sports Special Talent Class Program in High Schools - Rahayu Retnaningsih; Saryanto Saryanto; Awang Damar Dwi Prabowo (STAI Hubbulwathan Duri, 2023)
The objective of this study was to assess the efficacy of the sports special talent class programme at High School. This research employs a qualitative approach to evaluate programmes, utilising the Context, Input, Process, and Product (CIPP) model. The researcher served as the primary research instrument, in addition to employing interview standards, observation sheets, and document studies. The participants in the study consisted of school administrators, implementation supervisors, and trainers. Utilising data triangulation to employ advanced data analysis techniques. The study's findings can be succinctly summarised as follows: 1) Elements of the surrounding circumstances, specifically: The establishment of specialised sports talent classrooms is predicated on a directive issued by the Head of the Klaten District Education Office. 2) The process of admitting new pupils to exceptional sports talent programmes involves administrative selection, physical ability testing, and assessment of sports talents. The funding for organising specialised sports talent classes continues to depend on support from school operations and school committees. The state of field facilities owned by schools remains rudimentary, with some facilities being borrowed from external sources. The majority of coaches who specialise in sports fall into group B. There are multiple coaches who lack a trainer's licence. 3) The procedural element involves utilising a curriculum obtained from the Education Office. The time allotted for the process of cultivating talent and achieving sporting excellence is divided into categories B and C. 4) The product component refers to the sporting achievements attained by numerous kids at the district level. Provincial level always has representatives.